Fabrication of Quaternary High Temperature Shape Memory Alloys - Ahmed, H. Mustafa; Canbay, C. Aksu; Ozkul, I (Amer Inst Physics, 2019)
In today's technology, the useful materials attract more attention for sustainable of energy sources. Shape memory alloys (SMAs) are one of these useful materials due to their unique properties as pseudoelasticity and shape recovery property. SMAs can be classified as Cu-based (Cu-Zn, Cu-Al and Cu-Sn), Iron-based and NiTi. The copper-based system is the most useful because of easy fabrication and low cost production. In these systems, there are two main phases; martensite low symmetric temperature phase and austenite the high temperature phase. So the SMA got certain characteristic temperature that each phase starts and ends from high temperature to low temperature. There are many applications of these alloys as aerospace, medical, automobile, petroleum industry, sensors, actuators, etc. The characteristic transformation temperatures, the thermodynamic parameters and structural features of shape memory alloys (SMAs) are sensitive to variations in alloy composition, so in this study, we searched the effect of additive elements on the characteristic transformation temperatures, thermodynamic parameters and structure of Cu-Al based SMAs. In this context, Cu-12.9Al-22.73Be-0.37Mn (at%) alloy and Cu-18.73Al-21.06Be-0.13Mn (at%) alloy were studied here as structural and thermodynamical. Upon thermal analyses, they were classified as HTSMA since the martensitic transformation temperatures for both alloy became above 100 degrees C. Also the martensite phases were detected in both alloys by XRD measurements at room temperature.
35th International Physics Congress of the Turkish-Physical-Society (TPS) -- SEP 04-08, 2019 -- Bodrum, TURKEY